The Antioxidative Effect of Heat‐Shock Protein 70 in Dendritic Cells. (22nd August 2013) - Je, J. H.; Kim, D. Y.; Roh, H. J.; Pak, C.; Kim, D. H.; Byamba, D.; Jee, H.; Kim, T.‐G.; Park, J. M.; Lee, S.‐K.; Lee, M.‐G.
Abstract: Reactive oxygen species (ROS) are produced by dendritic cells (DCs) during antigen presentation in contact hypersensitivity (CHS). ROS cause a number of non‐enzymatic protein modifications, such as carbonylation. Carbonylated proteins in DCs in response to hapten have not been fully identified yet. To identify the proteins carbonylated by ROS, murine epidermis‐derived DC line XS106 was challenged with a hapten, 2, 4, 6‐trinitrobenzene sulphonic acid (TNBS). MALDI‐TOF analysis revealed that heat‐shock protein 70 (HSP70) was one of the carbonylated proteins induced by TNBS. To verify the role of HSP70 in TNBS‐treated XS106 cell, we fused protein transduction domain (PTD) with HSP70 to facilitate protein delivery into the cell. The transfected fusion protein HSP70 within the cell caused transient increase of the cellular level of HSP70. Transient increase of HSP70 level in XS‐106 DCs resulted in inhibition of ROS production, carbonylation of HSP70, p38 MAPK activation and subsequently IL‐12 secretion. To investigate the effects of PTD–HSP70 in vivo, ear‐swelling experiments with 2, 4, 6‐trinitro‐1‐chlorobenzene (TNCB) were performed in BALB/c mice. Pretreatment of PTD–HSP70 reduced the CHS response to TNCB in vivo . We report here that carbonylation of HSP70 by ROS is associated with the pathogenesis of CHS, suggesting possibility of HSP70‐targeting therapy in CHS.